Student and Teacher Outcomes of the Class-Wide Function-Related Intervention Team Efficacy Trial. (October 2016) - Wills, Howard; Kamps, Debra; Fleming, Kandace; Hansen, Blake
Schools continue to strive for the use of evidenced-based interventions and policies to foster well-managed classrooms that promote improved student outcomes. The present study examined the effects of the Class-Wide Function-related Intervention Teams (CW-FIT), a group contingency intervention, on the on-task and disruptive behavior of elementary school students with or at risk for emotional behavior disorders (EBD). Seventeen elementary schools, 159 general education teachers, and 313 students participated in the randomized-control group design study. Fidelity of implementation was strong for intervention group teachers and was measured across groups and throughout baseline conditions. Results suggest that CW-FIT can be used to increase on-task behavior and reduce the disruptive behavior of students with or at risk for EBD. In addition, teachers in intervention classes increased praise and reduced reprimands to individual students and along with their students, reported high levels of consumer satisfaction.